2021
DOI: 10.1111/cas.14980
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab plus pemetrexed‐platinum for metastatic nonsquamous non–small‐cell lung cancer: KEYNOTE‐189 Japan Study

Abstract: Pembrolizumab plus pemetrexed‐platinum significantly improved overall survival (OS) and progression‐free survival (PFS) with manageable safety compared with placebo plus pemetrexed‐platinum in patients with previously untreated metastatic nonsquamous non–small‐cell lung cancer (NSCLC) without EGFR/ALK alterations in the global, randomized, double‐blind, phase 3 KEYNOTE‐189 study. We present results of Japanese patients enrolled in the KEYNOTE‐189 global and Japan extension studies. Patients were randomized 2:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 18 publications
(48 reference statements)
8
38
1
Order By: Relevance
“…The consistent findings across subgroups and all randomized patients in this study are in line with prior studies that compared clinical outcomes of first-line immunotherapy for NSCLC between Asian and global populations. 27 , 28 , 29 , 30 , 31 , 32 , 33 In a subanalysis of Asian patients enrolled in CheckMate 9LA, first-line nivolumab plus ipilimumab in combination with two cycles of chemotherapy showed survival benefit over chemotherapy, consistent with results in all randomized patients. 30 , 31 Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients showed clinical benefits of first-line pembrolizumab plus chemotherapy over chemotherapy for metastatic squamous or nonsquamous NSCLC, respectively, consistent with results in the all randomized population of each study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The consistent findings across subgroups and all randomized patients in this study are in line with prior studies that compared clinical outcomes of first-line immunotherapy for NSCLC between Asian and global populations. 27 , 28 , 29 , 30 , 31 , 32 , 33 In a subanalysis of Asian patients enrolled in CheckMate 9LA, first-line nivolumab plus ipilimumab in combination with two cycles of chemotherapy showed survival benefit over chemotherapy, consistent with results in all randomized patients. 30 , 31 Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients showed clinical benefits of first-line pembrolizumab plus chemotherapy over chemotherapy for metastatic squamous or nonsquamous NSCLC, respectively, consistent with results in the all randomized population of each study.…”
Section: Discussionsupporting
confidence: 63%
“… 30 , 31 Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients showed clinical benefits of first-line pembrolizumab plus chemotherapy over chemotherapy for metastatic squamous or nonsquamous NSCLC, respectively, consistent with results in the all randomized population of each study. 27 , 28 , 32 , 33 Similarly, in a subgroup analysis of the KEYNOTE-024 study in Japanese patients with metastatic NSCLC and PD-L1 tumor proportion score ≥50%, pembrolizumab monotherapy showed survival benefit over platinum-based chemotherapy, consistent with the outcomes for all randomized patients in the study. 34 , 35 Cross-study comparisons should be made with caution, however, due to differences in patient populations, study design, and other key elements.…”
Section: Discussionmentioning
confidence: 53%
“…versus 45%, respectively), consistent with OS improvements observed in the all randomized population[29]. Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients also favored first-line combination immunotherapy with pembrolizumab plus chemotherapy over chemotherapy in Asian/Japanese patients with metastatic squamous or nonsquamous NSCLC, respectively, consistent with findings in the all randomized population of each study[2,3,27,28].…”
supporting
confidence: 78%
“…Chemotherapy for NSCLC is associated with interethnic differences in survival outcomes [ 23 ]; however, data directly comparing the efficacy of immunotherapy between Asian and global populations are limited. Some studies have shown clinical benefits of first-line immunotherapy combinations in both all randomized patients and the Asian subpopulation [ 27 29 ]. In a subanalysis of the phase 3 CheckMate 227 study in Asian patients with tumor PD-L1 expression ≥ 1% or < 1%, first-line treatment with nivolumab plus ipilimumab combination therapy demonstrated durable long-term survival and clinical benefits versus chemotherapy (median OS not reached versus 22.9 months; 2-year OS rate, 53% versus 45%, respectively), consistent with OS improvements observed in the all randomized population [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation